Complementary use of radiological skeletal survey and bone scintigraphy in detection of bony injuries in suspected child abuse. Issue 5 (1st May 2003) - Mandelstam, S A; Cook, D; Fitzgerald, M; Ditchfield, M R
Abstract : Aim: To compare the effectiveness of radiological skeletal survey and bone scintigraphy for the detection of bony injuries in cases of suspected child abuse. Methods: All cases with a discharge diagnosis of child abuse that presented to the Royal Children's Hospital between 1989 and 1998 were retrieved, and those children that had undergone both skeletal survey and bone scintigraphy (radioisotope bone scan) within a 48 hour period were included in this study. Both examinations followed rigid departmental protocols and protocols remained identical throughout the timeframe of the study. The reports of the skeletal surveys and bone scans were retrospectively reviewed by a paediatric radiology fellow and consultant paediatric radiologist. Results: The total number of bony injuries identified was 124 in 30 children. Of these, 64 were identified on bone scan and 77 on skeletal survey. Rib fractures represented 60/124 (48%) of the bony injuries and were present in 16/30 children (53%), of which 62.5% had multiple rib fractures. Excluding rib fractures, there were 64 (52%) bony injuries, of which 33% were seen on both imaging modalities, 44% were seen on skeletal survey only, and 25% were seen on bone scans alone. Metaphyseal lesions typical of child abuse were present in 20 cases (31%) on skeletal survey; only 35% of these were identified on bone scan. Six children (20%) had normal skeletal surveys, with abnormalities shown on bone scan. There were three children (10%) with normal bone scans who were shown to have injuries radiographically. Conclusions: Skeletal survey and bone scintigraphy are complementary studies in the evaluation of non-accidental injury, and should both be performed in cases of suspected child abuse.